Identification and localization of unknown seismic signals via reverse time migration within the Costa Rica Rift (2023)
The study was conducted in the Panama Basin, a zone with a complex system of mid-ocean ridges (MORs), explaining its intriguing thermal and seismic qualities and thereby making it an integral place for research. Similarly, the Panama Basin is a bathymetrically restricted oceanic basin situated in the Eastern Pacific near the subduction zone of Central and South America. A network of ocean bottom seismometers (OBS) was deployed in one of the mid ocean ridges, the Costa Rica Rift, and operated for 23 days from January 26 to February 16, 2015. Previous studies have used this data and discovered several microearthquakes following compelling spatiotemporal trends. Regardless, non-volcanic tremor indagation has remained quiet on this site. Non-volcanic tremors are the most familiar seismic waves detected during slow-slip events. They are weak continuous vibrations with no clear impulsive phases. We processed all available data from this network to investigate if non-volcanic tremors are occurring within the zone. To tackle the task, we developed a pipeline that consisted of generating seismograms, filtering them, extracting the event, and finally locating the events. We used the reverse time migration (RTM) technique to map the events since it detects and locates events with a low signal-to-noise ratio (SNR) with no need for phase identification or picking. We identified and mapped 226 possible tremor events in the vicinity of the Costa Rica Rift. They were compactly clustered around the southwest of the network, did not show temporal clusterization, and predominantly occurred on a day-by-day basis along the survey. The results are relevant since no non-volcanic tremor was reported either in that zone or in that tectonic setting (divergent margin). However, limited station availability in the last weeks and an incomplete location method could introduce biases in the results.